Quality of Service using Adaptive Traffic Balancing in Wireless (Ad Hoc) Mesh Networks - Aseri, Trilok Chand; Qureshi, Aslam (INFOCOMP Journal of Computer Science, 2008)
Wireless Mesh networks exploit multi-hop wireless communications between Access Points to replace wired infrastructure. For improving the performance of Quality of Service in face of unreliable wireless medium, an adaptive traffic balancing using traffic distribution algorithm has been proposed. In this paper, an adaptive traffic balancing is described to change the verification rule of the traffic state at each node dynamically, according to the number of collisions detected by the node. The simulation has been done to evaluate the developed algorithm. The results show that after deploying adaptive traffic balancing, performance is improved and the system resources are used more efficiently.